2021
DOI: 10.1016/j.ekir.2020.12.001
|View full text |Cite
|
Sign up to set email alerts
|

An International Delphi Survey on Exercise Priorities in CKD

Abstract: Introduction Defining the role of exercise in chronic kidney disease (CKD) is a top research priority for people with CKD. We aimed to achieve consensus on specific research priorities in exercise and CKD among an international panel of stakeholders. Methods Using the Delphi method, patients/caregivers, researchers, clinicians, and policymakers submitted their top research priorities in round 1 and ranked their importance in rounds 2 and 3 using a 9-point Likert scale. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…ESRD patient are more commonly sedentary and tend to avoid exercise ( 191 ); additionally, the dialysis population is more often aged, frail, depressive and with many comorbid conditions which are major obstacles to exercising. Finally, often the HD personnel has lack of expertise or resource to start an exercise program ( 192 ).…”
Section: Discussion: How To Overcome Anabolic Resistance In Dialysis-treated Patients?mentioning
confidence: 99%
See 2 more Smart Citations
“…ESRD patient are more commonly sedentary and tend to avoid exercise ( 191 ); additionally, the dialysis population is more often aged, frail, depressive and with many comorbid conditions which are major obstacles to exercising. Finally, often the HD personnel has lack of expertise or resource to start an exercise program ( 192 ).…”
Section: Discussion: How To Overcome Anabolic Resistance In Dialysis-treated Patients?mentioning
confidence: 99%
“…Several studies have addressed the issue of the efficacy of this combined treatment in HD patients [see ref. ( 192 ) for review]. Likewise, early studies in HD patients has showed that a single bout of either endurance or resistance exercise enhances the anabolic response to nutritional supplements ( 194 ).…”
Section: Discussion: How To Overcome Anabolic Resistance In Dialysis-treated Patients?mentioning
confidence: 99%
See 1 more Smart Citation
“…Since exercise therapy is the core of a comprehensive renal rehabilitation program, the relatively rich literature about exercise therapy for CKD patients was primarily reviewed. Thereafter, a number of systematic reviews for physical activity, renal function, lifestyle change in CKD including dialysis patients, as well as international surveys and editors' commentary, has been published in recent years [22][23][24][25][26][27][28][29][30][31][32].…”
Section: Guidelines For Renal Rehabilitationmentioning
confidence: 99%
“…Several studies on exercise as a treatment for sarcopenia using the Delphi method have been performed [ 23 , 24 ]. Research on exercise in other diseases, such as musculoskeletal or internal medicine, has also been conducted [ 25 , 26 , 27 , 28 , 29 ]. However, studies on exercise targeting patients with both stroke and preexisting sarcopenia are rare.…”
Section: Introductionmentioning
confidence: 99%